Differences in Correlation Values in Sex Determination based on Ridge Density of Hypothenar, External Ear Anthropometric and Canine Index - Iswara, Raja Al Fath Widya (Trends in Sciences, 2021)
Hypothenar region is an area that is often contacts with surfaces during activities, and the ear is proven to be more consistent than face identification in passive biometrics. While, the teeth are hardest part in the human body which covered inside the oral cavity. These 3 parts of the body have a great role forensic identification especially in determining sex. The aim of this study is to know differences in correlation values in sex determination based on ridge density of hypothenar region of the palm, external ear anthropometric and canine index. This was a cross sectional study with observational analytic design, include 500 medical students in Kariadi Hospital Semarang Central Java Indonesia, age 21 - 26 years old, who are included in inclusion criteria, male (n = 250), female (n = 250). Ridge density is measured by calculating the average number of hypothenar palm ridge on the side of the top, middle and bottom; each area is 5×5 mm2 in measurement. External ear anthrophometric consists ear length, ear breadth, base auricular, lobe length and lobe width. Canine index is calculated by dividing mesiodistal width and intercanine distance in 4 regions. Spearman correlation test between ridge density of hypothenar region palm prints, external ear anthropometric, mandibular canine index and sex shows significant correlation with p-value = 0.000. There is no significant difference between maxillary canine index and sex (right maxillary p-value = 0.112 and left maxillary p-value = 0.082). There are differences in correlation values in sex determination based on ridge density of hypothenar region palm prints, external ear anthropometric and mandibular canine index. Ridge density of hypothenar region palm prints and ear length are show strong correlation in sex determination.